Metabolic Syndrome and Its Associated Factors among Type 2 Diabetic Patients in Southwest Ethiopia, 2021/2022 - Dereje Gemeda; Endegena Abebe; Abdissa Duguma (Journal of Diabetes Research)
Background. Metabolic syndrome is one of the leading global public health and clinical challenges, with increasing prevalence figures ranging from 10% to as high as 84%. There is a 5-fold increase in metabolic syndrome associated with type 2 diabetes and a 2-fold increase associated with the development of cardiovascular disease. The calorie-dense diet and sedentary life patterns are the most important contributory factors that have been established. Objective. This study is aimed at assessing metabolic syndrome and its associated factors among patients with type 2 diabetes attending chronic follow-up units at hospitals in Southwest Ethiopia, in 2020. Methods. This study was conducted at hospitals in Southwest Ethiopia, using an institutional-based cross-sectional study design from September 1, 2020, to August 30, 2021. Data was collected from 422 type 2 diabetics through face-to-face interviews using structured and pretested questionnaires. Data were entered into Epi-data version 4.4.1 and exported for analysis to the Statistical Package for Social Sciences 25. The magnitude of metabolic syndrome was determined by using the National Cholesterol Education Program Third Adult Treatment Panel III criteria. Bivariate and multivariable logistic regression analyses were used to evaluate associated factors for the outcome variable. A P value of less than 0.05 was considered statistically significant. Result and Conclusion. Out of the 422 sample sizes, 394 type 2 diabetics participated in this study, giving a response rate of 93.36%. The overall prevalence of metabolic syndrome among type 2 diabetics in this study was 68.3%, using the National Cholesterol Education Program and Third Adult Treatment Panel criteria. The associated factors for metabolic syndrome among type 2 diabetics are urban residency, old age, physical inactivity, salt intake, inadequate fruit and vegetable consumption, palm oil, and eating meat.